ANALYSIS OF THE AVAILABILITY OF WATER RESOURCES AND CONSERVATION LESTI SUB-BASIN DISTRICT OF MALANG - Abdul Somat Bukori; Rachmat Boedisantoso (Journal of Civil Engineering, 2017)
Lesti sub basins is one of the upstream part of the Brantas river basin located in the district of Malang. ConditionsLesti sub-basins have been damaged thereby potentially Experiencing a water deficit. The deficit of water in the dry season in2017 Amounted to 2,141,057 m³ and 2023 Amounted to 3,881,593 m³. To overcome the deficit of water carried out an analysisof the conservation of water resources. This analysis is carried out, among others, plant conservation and mechanical.Conservation of vegetation done by planting of agarwood trees. While mechanically performed with rainwater harvestingwith the roof and the building of the embung. The results of the analysis of the required land area until the year 2023 with theplanting of agarwood trees covering an area of 18.27 km². Rainwater harvesting using roofs as much as 2 water storage tankswith a capacity each of 32 m³. Embung needs as much as 3 each reservoir capacity of 800,000 m³. Embung investment costsRp. 207,205,545,000 Done in 2017 until 2018.